ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst and preparation method and application thereof

By using ZIF-67/nitrogen doped molybdenum carbide heterojunction catalyst in lithium sulfur batteries, the problem of polysulfide ‘shuttle effect’ in lithium sulfur batteries is solved, and the cycle stability and energy density of the battery are significantly improved.

CN119517986AActive Publication Date: 2025-02-25CHONGQING INST OF GREEN & INTELLIGENT TECH CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411341350.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-25
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Lithium sulfur batteries have serious volume expansion problems during charging and discharging, resulting in damage to the electrode structure, and the poor conductivity of sulfur limits the electrochemical reaction rate, resulting in polysulfide 'shuttle effect', resulting in loss of active materials, rapid attenuation of capacity and Coulun’s efficiency declined.

Method used

Using ZIF-67/nitrogen doped molybdenum carbide heterojunction electrocatalyst, combined with high-temperature calcining technology, a heterojunction electrocatalyst with excellent electrochemical properties was prepared for lithium-sulfur battery positive electrode materials. Reduce the 'shuttle effect' of polysulfides.

Benefits of technology

It significantly improves the high-rate performance and cycle stability of lithium-sulfur batteries, accelerates the charging and discharge reaction kinetics, significantly reduces the "shuttle effect" of polysulfides, and extends the battery's cycle life and energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517986A_ABST
    Figure CN119517986A_ABST
Patent Text Reader

Abstract

The invention discloses a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst as well as a preparation method and application of the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst. The preparation method comprises the following steps: (1) dissolving 300mg of ammonium molybdate tetrahydrate in 100mL of water, adding 180mg of dopamine hydrochloride, stirring for 30 minutes, adding 200mL of absolute ethyl alcohol and 2mL of trihydroxymethyl aminomethane hydrochloride (Tris-HCl) buffer solution (the concentration is 1mol / L), adjusting the pH value to 8.5, and reacting for 12 hours; (2) freeze-drying after centrifugal cleaning, and calcining for 2 hours at the temperature of 650 DEG C and 3 hours at the temperature of 900 DEG C in an argon atmosphere to obtain N-Mo2C; (3) 186 mg of cobalt nitrate hexahydrate is dissolved in 5 ml of methanol, 205 mg of 2-methylimidazole is dissolved in 5 ml of methanol, 100 mg of N-Mo2C is dispersed in a 2-methylimidazole methanol solution, then a cobalt nitrate methanol solution is dropwise added, and a reaction is conducted for 4 hours at the normal temperature; and (4) freeze-drying after filtering and cleaning, and calcining for 3 hours at 750 DEG C in an argon atmosphere to prepare the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction catalyst material. The method is low in cost and simple and convenient in process, and the material shows excellent performance such as high rate and long cycle when applied to lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery catalyst materials, and specifically relates to a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst and a preparation method thereof and application in a lithium-sulfur battery. Background Art

[0002] Lithium-sulfur batteries (Li-S batteries) have great potential to become the next generation of high energy density energy storage devices due to their high theoretical energy density, low material cost and environmental friendliness. Compared with traditional lithium-ion batteries, the theoretical specific capacity of lithium-sulfur batteries is as high as 1675mAh·g -1 , and sulfur as a positive electrode material is not only abundant in resources and low in price, but also has low toxicity and little impact on the environment. Lithium-sulfur batteries have broad application prospects in electric vehicles, portable electronic devices, and energy storage systems.

[0003] However, the sulfur positive electrode of lithium-sulfur batteries has serious volume expansion problems during the charging and discharging process, which may lead to the destruction of the electrode structure. The poor conductivity of sulfur limits the rate of its electrochemical reaction and requires the assistance of conductive agents. In addition, lithium-sulfur batteries will produce polysulfides during operation. These intermediates are easily soluble in the electrolyte and diffuse to the lithium negative electrode, causing a "shuttle effect", which leads to the loss of active materials, rapid capacity decay and decreased coulombic efficiency. In addition, the dendrite growth problem of the lithium metal negative electrode may also cause short circuits and safety hazards. Summary of the invention

[0004] The present invention aims to solve the "shuttle effect" problem of sulfides in the above prior art and provides a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst and a preparation method thereof.

[0005] The technical solution adopted by the present invention is: a method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst, comprising the following steps:

[0006] Dissolve ammonium molybdate tetrahydrate in water, add dopamine hydrochloride, stir and mix thoroughly, then add anhydrous ethanol and Tris-HCl buffer solution (concentration is 1 mol / L), adjust the pH to 8.5, and react for 12 hours; centrifuge and wash, freeze-dry, and perform the first calcination under argon atmosphere to obtain N-Mo2C;

[0007] Cobalt nitrate hexahydrate is dissolved in methanol to obtain solution I, 2-methylimidazole is dissolved in methanol to obtain solution II, N-Mo2C is dispersed in solution II, stirred, and solution I is added dropwise, and the reaction is carried out at room temperature for 4 hours; after filtration and washing, the solution is freeze-dried, and calcined for the second time under an argon atmosphere to obtain a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst.

[0008] Specifically, the mass ratio of the ammonium molybdate tetrahydrate to dopamine hydrochloride is 3:1.5-2.

[0009] Furthermore, the pH is adjusted to 8.5 by adding ammonia water.

[0010] In the above scheme, the first calcination includes calcining at 650° C. for 2 hours at a heating rate of 5° C. / min, and then heating to 900° C. for calcining for 3 hours.

[0011] Furthermore, the second calcination includes calcining at 750° C. for 3 hours at a heating rate of 5° C. / min.

[0012] A ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst is prepared by the above-mentioned preparation method.

[0013] The present invention provides an application of a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst in preparing a lithium-sulfur battery. The ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst is used to prepare a positive electrode sheet.

[0014] Furthermore, the above application comprises the following steps:

[0015] (1) The ZIF-67 / nitrogen-doped molybdenum carbide heterojunction catalyst and sulfur were mixed uniformly in a mortar at a mass ratio of 2:8, transferred from the glove box to a reactor, and heated at 155° C. in an argon atmosphere for 12 hours to obtain a sulfur cathode material;

[0016] (2) mixing the sulfur positive electrode material: conductive carbon black: binder in a mass ratio of 8:1:1, adding N-methylpyrrolidone to the mixture, stirring for 12 hours, and applying the mixture on the surface of the carbon paper;

[0017] (3) placing the electrode obtained in step (2) in a vacuum drying oven for drying;

[0018] (4) using a cutting machine to cut the electrode sheet dried in step (3) to obtain a positive electrode sheet;

[0019] (5) Assemble the positive electrode shell, the positive electrode sheet prepared in step (4), 40 μL of lithium-sulfur electrolyte, polypropylene diaphragm, gasket and negative electrode shell into a battery in sequence, and the sulfur loading of the positive electrode sheet is 1.0-2.0 mg / cm 2 .

[0020] Finally, the present invention provides a positive electrode material for a lithium-sulfur battery, comprising a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst and sulfur in a mass ratio of 2:8.

[0021] The advantages and beneficial effects of the present invention are as follows:

[0022] According to the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst for lithium-sulfur batteries and the preparation method thereof involved in the present invention. A heterojunction electrocatalyst with excellent electrochemical performance is prepared by combining a chemical solution method with a high-temperature calcination technology. The lithium-sulfur battery catalyst material of the present invention is applied to the positive electrode material of a lithium-sulfur battery. The chemical solution method is combined with the high-temperature calcination technology to produce a synergistic effect, which can greatly improve the high-rate performance and cycle stability of the battery, accelerate the charge and discharge reaction kinetics, and significantly reduce the "shuttle effect" of polysulfides. Its preparation process is simple, low-cost, and environmentally friendly, and it has important application prospects and potential industrialization value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a TEM image of a lithium-sulfur battery catalyst material in an embodiment of the present invention;

[0024] Figure 2 The lithium-sulfur battery using the catalyst material in the embodiment of the present invention has a 0.1 mV·s -1 Cyclic voltammetry curves at the scan rate;

[0025] Figure 3 is a graph of the discharge specific capacity of a lithium-sulfur battery using the catalytic material under 1C rate conditions in an embodiment of the present invention;

[0026] Figure 4 is a charge and discharge curve diagram of a lithium-sulfur battery using the catalytic material under 1C rate conditions in an embodiment of the present invention;

[0027] Figure 5 is a graph of the discharge specific capacity of a lithium-sulfur battery using the catalyst material under different rate conditions in an embodiment of the present invention;

[0028] Figure 6 is a Li2S deposition curve graph using catalyst materials in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] The following will describe the technical solutions in the embodiments of the present invention in detail in conjunction with the accompanying drawings in the embodiments of the present invention. The described embodiments are only part of the embodiments of the present invention.

[0030] The present invention provides a method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst, which can be used in the field of lithium-sulfur batteries, especially for the problems of "shuttle effect" of polysulfide in lithium-sulfur batteries and poor stability under high current conditions. The synthesis process of the electrocatalyst material in the embodiment of the invention comprises the following steps: dissolving 300 mg of ammonium molybdate tetrahydrate in 100 mL of deionized water, adding 180 mg of dopamine hydrochloride and stirring for 30 minutes, then adding 200 mL of anhydrous ethanol and 2 mL of 1 mol / L Tris-HCl buffer solution and continuing to stir for 20 minutes, then adjusting the pH to 8.5 with ammonia water and reacting for 12 hours. The reacted solution is centrifuged, washed with anhydrous ethanol and water, respectively, and freeze-dried. Then, in an argon atmosphere, at a heating rate of 5 ° C / min, first calcined at 650 ° C for 2 hours, then heated to 900 ° C for 3 hours to obtain N-Mo2C. Afterwards, 186 mg of cobalt nitrate hexahydrate was dissolved in 5 mL of methanol, 205 mg of 2-methylimidazole was dissolved in 5 mL of methanol, 100 mg of N-Mo2C was dispersed in 2-methylimidazole methanol solution, and cobalt nitrate methanol solution was added dropwise, reacted at room temperature for 4 hours, filtered and washed, and freeze-dried. Finally, ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst was prepared by calcining at 750 ° C for 3 hours at a heating rate of 5 ° C / min in a high-purity argon gas flow. The positive electrode, negative electrode, electrolyte and diaphragm of the present invention are according to the method commonly used by those skilled in the art (so it is not repeated here).

[0031] The application of the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalytic material in the above embodiment on the lithium-sulfur battery is specifically as follows: (1) the catalyst obtained above and sulfur are mixed in a mortar in a ratio of 2:8, transferred to a reactor, and heated at 155°C for 12 hours to obtain an active material; (2) active material: conductive carbon black: binder = 8:1:1 are mixed evenly, a certain amount of NMP is added to the mixture, and after stirring for 12 hours, the mixture is coated on the surface of carbon paper, and the coating thickness is 7 microns; (3) the coated electrode is placed in a vacuum drying oven at a temperature of 60°C for 12 hours to fully dry the electrode; (4) the electrode is cut into discs with a diameter of 12 mm using a cutting machine, and the mass of the electrode is weighed. (5) the positive electrode shell, the positive electrode obtained in step (4), 40 μL of lithium-sulfur electrolyte, polypropylene diaphragm, gasket and negative electrode shell are assembled into a battery in sequence, and the sulfur loading of the positive electrode is 1.0-2.0 mg·cm -2 .

[0032] Depend on Figure 1It can be seen that the microscopic morphology of the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalytic material shows obvious metal particles. The large metal particles are cobalt, and the small metal particles are molybdenum. A heterostructure is formed between the interfaces, which can effectively promote the reaction kinetics of sulfur conversion, reduce the "shuttle effect" caused by the dissolution of polysulfides, and improve the electrochemical performance of lithium-sulfur batteries.

[0033] After electrochemical performance testing, Figure 2 0.1mV·s -1 Two pairs of obvious redox peaks can be seen in the cyclic voltammetry curve at the scanning rate.

[0034] Figure 3 This is the long cycle curve under 1C high rate conditions. The first cycle discharge capacity is 847.2 mAh g -1 After 1000 cycles, the capacity is still maintained at 393 mAh g -1 , the average decay rate per cycle is only 0.076%.

[0035] Figure 4 These are the charge and discharge curves of the 1st, 100th, 300th, 500th, 700th, and 900th cycles of the battery, respectively. It can be seen that the lithium-sulfur battery has an obvious charge and discharge platform.

[0036] Figure 5 The charge and discharge curves at 0.2C, 0.5C, 1C, 2C, 5C and 10C conditions show that under the 5C high rate condition, the discharge capacity of the battery is 518.2mAh g -1 At 10C high rate, the battery’s discharge capacity is still 392.8 mAh g -1 , after returning to low rate conditions, the battery capacity can still remain at the same level as before.

[0037] Figure 6 This is the Li2S deposition curve on the catalyst electrode. It can be seen that the Li2S deposition capacity is 420.92 mAh g -1 , significantly improving the catalytic ability for polysulfide conversion.

[0038] Through electrochemical testing, the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst demonstrated excellent performance and application prospects, significantly improved the cycle life and energy density of the battery, and effectively suppressed the "shuttle effect" in lithium-sulfur batteries.

Claims

1. A method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst, characterized in that: The following steps are involved: Dissolve ammonium molybdate tetrahydrate in water, add dopamine hydrochloride, stir and mix thoroughly, then add anhydrous ethanol and Tris-HCl buffer solution, adjust the pH to 8.5, and react for 12 hours; centrifuge and wash, freeze-dry, and perform the first calcination under argon atmosphere to obtain N-Mo2C; Cobalt nitrate hexahydrate is dissolved in methanol to obtain solution I, 2-methylimidazole is dissolved in methanol to obtain solution II, N-Mo2C is dispersed in solution II, stirred, and solution I is added dropwise, and the reaction is carried out at room temperature for 4 hours; after filtration and washing, the solution is freeze-dried, and calcined for the second time under an argon atmosphere to obtain a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst.

2. The method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst according to claim 1, characterized in that: The mass ratio of the ammonium molybdate tetrahydrate to dopamine hydrochloride is 3:1.5-2.

3. The method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst according to claim 1, characterized in that: The pH was adjusted to 8.5 by adding aqueous ammonia.

4. The method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst according to claim 1, characterized in that: The first calcination includes calcining at 650° C. for 2 hours at a heating rate of 5° C. / min, and then heating to 900° C. for 3 hours.

5. The method for preparing a ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst according to claim 1, characterized in that: The second calcination includes calcining at 750° C. for 3 hours at a heating rate of 5° C. / min.

6. A ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst according to claim 6 in the preparation of lithium-sulfur batteries.

8. The application according to claim 7, characterized in that: The ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst is used to prepare a positive electrode sheet.

9. The use according to claim 7 or 8, characterized in that: The following steps are involved: (1) The ZIF-67 / nitrogen-doped molybdenum carbide heterojunction catalyst and sulfur were mixed uniformly in a mortar at a mass ratio of 2:8, transferred from the glove box to a reactor, and heated at 155° C. in an argon atmosphere for 12 hours to obtain a sulfur cathode material; (2) mixing the sulfur positive electrode material: conductive carbon black: binder in a mass ratio of 8:1:1, adding N-methylpyrrolidone to the mixture, stirring for 12 hours, and applying the mixture on the surface of the carbon paper; (3) placing the electrode obtained in step (2) in a vacuum drying oven for drying; (4) using a cutting machine to cut the electrode sheet dried in step (3) to obtain a positive electrode sheet; (5) Assemble the positive electrode shell, the positive electrode sheet prepared in step (4), 40 μL of lithium-sulfur electrolyte, polypropylene diaphragm, gasket and negative electrode shell into a battery in sequence, and the sulfur loading of the positive electrode sheet is 1.0-2.0 mg / cm 2 .

10. A positive electrode material for a lithium-sulfur battery, characterized in that: It comprises the ZIF-67 / nitrogen-doped molybdenum carbide heterojunction electrocatalyst as described in claim 6 and sulfur, with a mass ratio of 2:8.

Citation Information

Patent Citations

  • Graphene nanobelt vertical array-molybdenum carbide nanometer crystal composite material and its preparation method and use

    CN104588058A

  • Preparation method and application of bifunctional electrocatalyst of molybdenum disulfide composite material

    CN110026210A

  • Molybdenum carbide modified hollow nitrogen-doped carbon particles as well as preparation method and application thereof

    CN114956038A

  • Preparation method of nitrogen-doped carbon-coated molybdenum disulfide / cobalt octasulfide nano composite material and prepared battery positive electrode material

    CN115784200A

  • Nitrogen-doped molybdenum carbide and carbon composite nanomaterial and preparation method thereof

    CN115947342A